2004
DOI: 10.1111/j.1365-2095.2004.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural free gossypol and gossypol-acetic acid on growth performance and resistance of channel catfish (Ictalurus punctatus) to Edwardsiella ictaluri challenge

Abstract: A study was conducted to evaluate the effect of free gossypol from glanded-cottonseed meal (G-CSM) (natural free gossypol) or gossypol-acetic acid on growth performance, body composition, haematology, immune response and resistance of channel catfish (Ictalurus punctatus) to Edwardsiella ictaluri challenge. Soya bean meal-based diets supplemented with 0, 100, 200, 400, and 800 mg kg )1 free gossypol from G-CSM or gossypol-acetic acid were fed to juvenile channel catfish in triplicate aquaria to apparent satiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
2
15
0
2
Order By: Relevance
“…However, none of these mechanisms have been confirmed in fish because of some contradictory (Yildirim et al 2004) and complicated (Barros et al 2002) results on the hematological values.…”
Section: Discussionmentioning
confidence: 88%
“…However, none of these mechanisms have been confirmed in fish because of some contradictory (Yildirim et al 2004) and complicated (Barros et al 2002) results on the hematological values.…”
Section: Discussionmentioning
confidence: 88%
“… 23 reported that juvenile channel catfish could tolerate up to 900 mg free gossypol/kg diet from either cottonseed gossypol or gossypol acetic acid. No adverse effects on weight gain and feed utilization were observed when juvenile channel catfish were fed a soybean meal based‐diet supplemented up to 800 mg gossypol/kg diet 51 . Mbahinzireki et al.…”
Section: Discussionmentioning
confidence: 99%
“…Yildirim et al (2003) reported immunomodulation (improved macrophage chemotaxis ratio, serum lysozyme activity) and increased resistance of juvenile catfish (Ictalurus punctatus) to Edwardsiella ictaluri challenge at levels of 900 mg gossypol kg -1 or higher of a casein-gelatin based diet. However, in a later study no differences to E. ictaluri challenge were observed in juvenile catfish fed up to 800 mg gossypol kg -1 of a soy-based diet (Yildirim-Aksoy et al, 2004).…”
Section: Biological Effects In Fishmentioning
confidence: 99%